Venezuela from Chavez: cultural and political identities - Römer Pieretti, Max (Historia y Comunicación Social, 2014)
Venezuelan democracy in the late twentieth and early twenty–first century has been marked by the figure of Hugo Chávez Frías. Since a coup attempt against then President Carlos Andrés Pérez, until his death, defined the cultural and political identity of the country with their particular style and, above all, with the use of social media as major shapers of the imaginary collective. The analysis focuses on understanding the Venezuelan identity based study in what author’s considers the communicative milestones of the twenty years of Commander Chavez in Venezuela and universal public arena.